1993
DOI: 10.1037/0022-3514.64.6.1042
|View full text |Cite
|
Sign up to set email alerts
|

Self-discrepancy and natural killer cell activity: Immunological consequences of negative self-evaluation.

Abstract: The study tested whether self-discrepancy theory could account for changes in natural killer (NK) cell activity after exposure to self-referential stimuli. Anxious, dysphoric, and control Ss were pretested and 1 month later covertly exposed to their own self-guides as well as those of another S. Blood samples were drawn for analysis of NK cytotoxicity and cortisol. The dysphoric Ss manifested the greatest actual:ideal discrepancy, whereas the anxious Ss manifested the greatest actual:ought discrepancy. Content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 37 publications
(60 reference statements)
2
42
0
Order By: Relevance
“…BDI scores of the primary infertile group was significantly lower than those of the secondary infertile group. On the other hand immunological investigations on psychoneurosis have demonstrated the potential impact of psychological factors on immunity (22,23). For instance, natural killer cell (NK) activity has been determined as the main factor in premature termination of pregnancy (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…BDI scores of the primary infertile group was significantly lower than those of the secondary infertile group. On the other hand immunological investigations on psychoneurosis have demonstrated the potential impact of psychological factors on immunity (22,23). For instance, natural killer cell (NK) activity has been determined as the main factor in premature termination of pregnancy (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, idiographically elicited attributes predict affective, behavioural and/or physiological reactions more robustly than nomothetically identified self-attributes (e.g. Moretti & Higgins, 1990;Strauman et al, 2001;Strauman, Lemieux, & Coe, 1993;Shah, 2003). When the participant has completed all the SQ sheets prepared by the researcher (e.g.…”
Section: The Selves Questionnairementioning
confidence: 98%
“…Higgins (1990) has shown that people interpret social information on the basis of chronically accessible as well as recently activated constructs and that their emotions reflect discrepancies between various types of self-representations or self-schemas. Strauman and his colleagues ( Strauman, 1992 ;Strauman, Lemieux, & Coe, 1993 ) have demonstrated that such discrepancies not only distinguish different kinds of patients (anxious vs. depressed) but even predict immune response when confronted with different kinds of self-relevant information.…”
Section: The Role Of Mental Representations Of the Self Others And mentioning
confidence: 99%